Sentiment Analysis through Search Engine Trends for Green Marketing and Affiliate Terms: A Region Based Geographical Analysis: Exploring Sentiments and Regions in Green Marketing and Affiliate Terms: A Study of Google Users in India (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The key purpose of this exploratory research is to determine the interest of the Google users towards the green productsmarketing and causes and affiliate concepts of green products in India in the period from May 2017 to May 2018. Google trends are progressively used in various opinion finding functions to understand public attitude. We run Google trends for certain keywords which represent our variables that are relevant to Green Marketing. As the next step, we compare the interest towards various affiliated keywords for the pre-determined time frame. Afterwards a geographical regional analysis related to identify keywords is performed for various Indian states so as to identify the most interest geographical regions in our selected variables. The findings of the study have allowed us to recognize important ‘green’ keywords that most concern people based on seasons and regions in India.